Aspartic acid racemization dating of Holocene brachiopods and bivalves from the southern Brazilian shelf, South Atlantic - Wood, Susan L. Barbour; Krause, Richard A.; Kowalewski, Michal; Wehmiller, John; Simões, Marcello Guimarães [UNESP] (Elsevier B.V., 2006)
The extent of racemization of aspartic acid (Asp) has been used to estimate the ages of 9 shells of the epifaunal calcitic brachiopod Bouchardia rosea and 9 shells of the infaunal aragonitic bivalve Semele casali. Both taxa were collected concurrently from the same sites at depths of 10 m and 30 m off the coast of Brazil. Asp D/L values show an excellent correlation with radiocarbon age at both sites and for both taxa (r(Site)(2) (9) (B. rosea) = 0.97 r(Site)(2) (1) (B.) (rosea) = 0.997, r(Site)(2) (9) (S.) (casali) = 0.9998, r(2) (Site) (1) (S.casali) = 0.93). The Asp ratios plotted against reservoir-corrected AMS radiocarbon ages over the time span of multiple millennia can thus be used to develop reliable and precise geochronologies not only for aragonitic mollusks (widely used for dating previously), but also for calcitic brachiopods. At each collection site, Bouchardia specimens display consistently higher D/L values than specimens of Semele. Thermal differences between sites are also notable and in agreement with theoretical expectations, as extents of racemization for both taxa are greater at the warmer, shallower site than at the cooler, deeper one. In late Holocene marine settings, concurrent time series of aragonitic and calcitic shells can be assembled using Asp racemization dating, and parallel multi-centennial to multi-millennial records can be developed simultaneously for multiple biomineral systems. (c) 2006 University of Washington. All rights reserved.
Keywords: amino acid racemization; aspartic; radiocarbon dating; brachiopods; Bouchardia; mollusks; Semele; Holocene; Brazil; Ubatuba Bay